2016
DOI: 10.1007/s40071-016-0146-x
|View full text |Cite
|
Sign up to set email alerts
|

Complete replacement of fish meal by other animal protein sources on growth performance of Clarias gariepinus fingerlings

Abstract: To completely replace the fish meal by a mixture of earthworm and maggot meals, experimental diets were tested during 42 days on Clarias gariepinus fingerlings. Five isoproteic and isoenergetic diets (40 % crude protein and 17.9 ± 0.3 kJ g-1) including the control diet (D1) based on fish meal, were formulated. All these diets satisfied the essential amino acids requirements of C. gariepinus fingerlings. These diets were tested on triplicate groups of 50 fishes (initial body weight: 3 ± 0.1 g) bred in tank (0.5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 22 publications
(24 reference statements)
2
16
0
Order By: Relevance
“…The highest value obtained was in MD larvae fed with a mix of soya bean cake and chicken viscera (Djissou et al . ). Considering the results of Zhao et al .…”
Section: Amino Acids: Indispensable Amino Acid (Iaa) Contents and Digmentioning
confidence: 97%
“…The highest value obtained was in MD larvae fed with a mix of soya bean cake and chicken viscera (Djissou et al . ). Considering the results of Zhao et al .…”
Section: Amino Acids: Indispensable Amino Acid (Iaa) Contents and Digmentioning
confidence: 97%
“…Although amino acids profiles of D1 and D2 met the requirements of culture fish (Wilson & Moreau, 1996), fish fed with D2 exhibited high growth performance than those fed with D1. Previous authors (Alegbeleye et al, 2012;Collins, Overland, Skrede & Drew, 2013;Djissou, Adjahouinou, Koshio & Fiogbe, 2016;Sogbesan & Ugwumba, 2008) reported that combine protein sources improve the growth performances of fish better than single protein source, resulting from the synergism when various dietary protein sources are mixed in feeds. Indeed, D1 contained only one animal protein source (FM) when D2 contained two (FM and CBM).…”
Section: Discussionmentioning
confidence: 99%
“…Growth performance and feed utilization on fry 25% and 50% Vodounnou, Juste, et al (2016) African catfish (Clarias gariepinus) Growth performances and feed utilization in fingerlings Ratio of 2:5 mixed with maggots Djissou et al (2016) Rainbow trout (Oncorhynchus mykiss) Growth performance 25% and 50% Velásquez, Ibanez, Herrera and Oyarzun (1991) Common carp (Cyprinus carpio) Growth performance and feed efficiency 1:1 with Musca domestica larvae Coroian et al (2015) Chinese shrimp (Penaeus chinensis) Growth and survival Liu (2006) White shrimp (Penaeus vannamei) Growth performance and muscle nutritional Chiu et al (2015) Catfish (Clarias gariepinus) Growth and survival Zakaria et al (2012) Tilapia (Oreochromis mossambicus) Fry growth 36% vermiliquid Rameshguru and Govindarajan (2011) by Popek, Łuszczek and Rościszewska (1996) on Carassius auratus while the highest (100%) was achieved by Kostecka and Pączka (2006) on Gupy (Poecilia reticulata). Nevertheless, the 10% inclusion of E. fetida meal by Popek et al (1996) doubled the reproduction of the C. auratus.…”
Section: Utilization Of E Fetida In Fish Feed Processingmentioning
confidence: 99%
“…Also, when formulating fish feed, mixing the worm with other feed ingredients such as soy bean or barley can be an option to balance the essential amino acid profiles. Djissou, Adjahouinou, Koshio and Fiogbe (2016) mixed E. fetida with maggot and were able to completely replace fish meal. The authors obtained the best growth performance and feed utilization in C. gariepinus from the mixture compared to the fish meal.…”
Section: Utilization Of E Fetida In Fish Feed Processingmentioning
confidence: 99%